Supplementary potassium sulfate and potassium chloride fertilizers on yield and quality of Fujisawa Melon (Cucumis melo L.) - Saengngam, Thamthawat; Karuna , Suchada; Bootpetch, Sirisuda; Inboonchuay, Tawatchai; Pongsivapai, Pongpet (Asia-Pacific Journal of Science and Technology, 2025)
A completely randomized design was applied to investigate the effects of potassium sulfate and potassium chloride fertilizers on the yield and quality of Fujisawa melon (Cucumis melo L.). There were 9 treatments, 3 replicates. The treatments were: no potassium fertilizer (T1), soil-applied potassium sulfate (K2SO4) at a rate of 3.6 g/plant (T2), soil-applied potassium chloride (KCl) at 3.0 g/plant (T3), foliar-applied K2SO4 at 1.2 g/plant/time (T4), foliar-applied KCl at 1.0 g/plant/time (T5), soil-applied K2SO4 at 1.8 g/plant + foliar-applied K2SO4 at 0.6 g/plant/time (T6), soil-applied KCl at 1.5 g/plant + foliar-applied KCl at 0.5 g/plant/time (T7), soil-applied K2SO4 at 1.8 g/plant + foliar-applied KCl at 0.5 g/plant/time (T8), and soil-applied KCl at1.5 g/plant + foliar-applied K2SO4 at 0.6 g/plant/time (T9). The results revealed that T5 and T4 produced the highest skin thickness and weight of melon fruits. The highest content of total soluble solids (TSS) was observed in T2. The potassium content in the plant parts significantly influenced both the yield and quality components of the melon fruits, particularly impacting the quantity of TSS. Furthermore, the sulfur content, derived from K2SO4, was positively correlated with the quantity of TSS. The application of KCl as fertilizer increased the potassium levels in both the fruit flesh and peel. Additionally, the chloride content in the melon fruit flesh increased, influencing the flesh thickness and contributing to higher fruit weight.